Omega-3 and ranibizumab for age-related macular degeneration: A systematic review protocol. Issue 13 (March 2019) - Meng, Yan; Liu, Hong-wei; Sun, Peng; Zhou, Ping-ping; Wang, Jian-jie
Abstract: Background: Omega-3 and ranibizumab (O3R) has been reported to treat age-related macular degeneration (ARMD) effectively. However, up to the present, no systematic review specifically addressed the efficacy of O3R for the treatment of ARMD. Therefore, in this study, we will propose to assess the efficacy and safety of O3R for the treatment of ARMD. Methods: We will search PUMBED, EMBASE, CINAHI, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Cochrane Library, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, VIP Information, Wanfang Data, as well as the gray literature from inception up to the present. We will accept randomized controlled trials for assessing the efficacy and safety of O3R for ARMD. The primary outcomes include change in best corrected visual acuity and central retinal thickness. The secondary outcomes consist of changes in subfoveal choroidal thickness, macular atrophy, retinal average sensitivity, contrast sensitivity, glare disability, and quality of life. In addition, incidence and severity of adverse events will also be evaluated. Cochrane Collaboration tool will be used to assess the risk of bias for each included study. In addition, Grading of Recommendations Assessment, Development, and Evaluation tool will be utilized to assess the overall strength of the evidence. Two authors will independently carry out all procedures and any divergences will be solved through discussion with a third author. If it is possible, we will conduct meta-analysis and subgroup analysis concerning different interventions, risk of bias, and outcome measurements. Results: In this proposed study, we outline details of the aims and methods of efficacy and safety of O3R for the treatment of ARMD. Conclusion: The findings of this systematic review will summarize current evidence of O3R for the treatment of patients with ARMD. Dissemination and ethics: The results of the present study are expected to be published by peer-reviewed journals. This is a literature-based study. Thus, ethical approval is unnecessary for this study. Systematic review registration: PROSPERO CRD42019121177.